A proteção dos conhecimentos tradicionais associados à biodiversidade na América Latina: uma análise das legislações do Brasil e do Equador - Golart, Eduarda Aparecida Santos (2022)
The traditional knowledge associated with biodiversity is all the knowledge that comes from the traditional people and their exchange with their natural environment. This knowledge reveals existing diverse functions in the genetic resources present in biodiversity and as consequence become targets of interest to companies. The agriculture, pharmaceutical and food industry – mainly – have as objective to access traditional knowledge as means to discover genetic resources with the potential to manufacture products and processes, which can be patented and explored whit exclusivity. This context has made traditional knowledge unduly appropriated in recent decades, bringing to light the necessity to protect them. In the international sphere, the regulamentation of the access to genetic resources and the associated traditional knowledge is mainly given through the TRIPS Deal and the Convention on Biological Diversity (CBD). Both international norms need to be regulated by it’s members states. In this sense surges Law nº 13.123 of 2015 in Brazil, with intent to substitue the Provisional Measure nº 2.186 of 2001 which used to regulate the topic. In light of this new legislation and the necessity to secure norms that bring effective protection to the acossieted traditional knowledge, which are being unduly appropriated in the name of capitalism and economy, comes the following questioning: It’s possible to affirm that the advent of Law nº 13.123/2015 represented advances in the protection of traditional knowledge associated with biodiversity in Brazil? To what extent the advances already verified in Ecuador can be utilized as paradigms to the protection of traditional knowledge in Brazil? In light of the proposed problematic, the objective of the present study consists in analysing the protection of traditional knowledge associated with biodiversity in Latin America, from the legislations of Brazil and Ecuador. It becomes imperative to look at another country, especially in Latin America, with the intent to understand how the protection of traditional knowledge works and seek reflections about the reality in Brazil. For better development of the research the approaching method chosen is the deductive, as procedure bibliographical and documental analysis, the research technique employed is elaboration of summaries and records, lastly the adequate base theory is complex-systematic. Law 13.123 of 2015 brought innumerable alterations in regards to the protection of traditional knowledge, specially about the necessity of previous consent and sharing of benefits. The mentioned law creates exemptions front these instruments, which can weaken the desired protection. In regards to Ecuador, it counts with a Commom Access Regime to genetic resources and a Organic Code of Social Economy of Knowledge, which foresees a series of indispensable requirements to the access of associated traditional knowledge. Shows itself more apt to protect and grant rights to traditional people, in this manner the advance of the aforementioned Laws can contribute to reinforce the protection of traditional knowledge in Brazil.